High Level Security with Optimal Time Bound Ad-Hoc On-demand Distance Vector Routing Protocol (HiLeSec-OptiB AODV) - Karthikeyan, B; Hari Ganesh, S; Sathiaseelan, JGR; Kanimozhi, N (International Journal of Computer Sciences and Engineering, 2025)
The most wanted wireless networks is Mobile Ad hoc Network (MANET). MANET can configure easily without any infrastructure which one is used by at present as an infrastructure oriented wired or wireless network. It is one of the infrastructures less network consist of mobile devices. Individually each and every device in the Mobile ad hoc network will act as a router as well as node which provide the flexibility in the physical topology, optimal routing and data communication. In this paper the proposed HiLeSec-OpTiB AODV is the combination of En-SIm and OpTiB AODV. This combined algorithm is tested with intruders(active and passive attackers). This proposed HiLeSec-OpTiB AODV is implemented and tested by the use of OmNet++.